2023
DOI: 10.1063/5.0134858
|View full text |Cite
|
Sign up to set email alerts
|

Toward achieving cost-effective hexagonal BN semi-bulk crystals and BN neutron detectors via halide vapor phase epitaxy

Abstract: Presently, thermal neutron detectors fabricated from boron-10 enriched hexagonal boron nitride (h-10BN) ultrawide bandgap semiconductor grown by metal organic chemical vapor deposition (MOCVD) hold the record high detection efficiency among all solid-state detectors at 59%. To overcome the short comings of MOCVD growth, including inherently low growth rate and unavoidable impurities such as carbon in metal organic source, we demonstrate here the growth of natural hexagonal boron nitride (h-BN) semi-bulk wafers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The h-BN semi-bulk wafers used in this study were produced by HVPE. Natural boron trichloride (BCl 3 ) and NH 3 were used as precursors for B and N, respectively, and H 2 was used as a carrier gas [41]. The growth was conducted on a c-plane sapphire of 2-inches in diameter.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The h-BN semi-bulk wafers used in this study were produced by HVPE. Natural boron trichloride (BCl 3 ) and NH 3 were used as precursors for B and N, respectively, and H 2 was used as a carrier gas [41]. The growth was conducted on a c-plane sapphire of 2-inches in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the metal-organic chemical vapor deposition (MOCVD) growth technique, the precursors used in HVPE growth contain no carbon impurities and it provides a faster growth rate than MOCVD. Due to h-BN's layered structure, a thick h-BN wafer self-separates from the sapphire substrate after growth during the process of cooling down, from which a freestanding h-BN wafer was obtained [28,38,[40][41][42]. A micrograph of a representative freestanding h-BN wafer of 2-inches in diameter is shown in Figure 1a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BN is a white, crystalline ceramic, commonly with a hexagonal crystal structure similar to that of graphite. Boron nitride has a wide range of applications, e.g ., lubricant, electrical insulators, thermal conductors, and deep ultraviolet (UV) emitter . Boron nitride is a well-known wide band gap semiconductor and has been successfully introduced for deep UV and neutron detection, benefiting from the decent charge transport properties (high sensitivity) and high resistivity (low noise level), making them ideal candidates for photodetection. For instance, Kaushik et al reported deep-ultraviolet photodetectors based on hexagonal boron nitride nanosheets and enhanced the device performance by localized surface plasmon resonance with Al nanoparticles . Liu and co-authors fabricated high-performance deep ultraviolet photodetectors based on few-layer hexagonal boron nitride and achieved ultra-high on/off ratio of >10 3 .…”
Section: Introductionmentioning
confidence: 99%
“…31 The recorded PALS lifetime is commonly used to determine the size and open volume of the defects. 32 Figure 3a schematically depicts the PALS setup, the source 22 Na was placed between the BN samples, and the emitted gamma rays were collected with two commercial detectors with different characteristic peak energies. The recorded positron lifetime is highly sensitive to the localized states of the testing samples, and the lifetime normally increases within the vacancies.…”
mentioning
confidence: 99%